Number of People Required for Usability Evaluation: The 10±2 Rule. - HWANG, WONIL; SALVENDY, GAVRIEL (Communications of the ACM, 2010)
The article discusses the number of personnel needed to test the usability of software products. The authors discusses different methods of usability evaluation, including think aloud (TA), in which the reactions of test users to products are recorded in a laboratory, heuristic evaluation (HE), in which test users evaluate user interfaces based on established usability principles, and cognitive walkthrough (CW), in which the steps for the performance of a task are examined for usability problems. The use of meta-analysis and regression analysis to determine sample sizes for usability studies is discussed.